Premedication with Dexmedetomidine versus Midazolam for Prevention of Emergence Delirium in Children - Ahmed, Waqar; Khan, M. Umair; Yasin, Bilal; Saeed, Muhammad; Tariq, Waqas; Fazal, Fazal Hussain (Pakistan Armed Forces Medical Journal, 2024)
Objective: To determine the effects of premedication with Dexmedetomidine vs. Midazolam to prevent the emergence of delirium in children operated at our hospital.Study Design: Quasi-experimental study.Place and Duration of Study: Anaesthesia and Pain Medicine Department, Combined Military Hospital, Okara Pakistan, from Apr 2021 to May 2022.Methodology: Children who operated in the main operation theatre of our hospital without any complications during the study period were recruited for this comparison of two medications to prevent the emergence of delirium. Study participants were allocated to two groups: Group-A received premedication with Dexmedetomidine, and Group-B received Midazolam in standard doses. An independent assessor assessed post-operative delirium using the Pediatric Anesthesia Emergence Delirium Scale.Results: A total of 130 children were included in the study, and they met the inclusion/exclusion criteria. The mean age of the children in the study was 5.66±3.55 years. 80(61.5%) patients were male, while 50(38.5%) were female. 29(22.3%) children showed the presence of emergence delirium, while 101(77.7%) did not show the presence of emergence delirium on the Pediatric Anesthesia Emergence Delirium Scale. It was revealed that children in Group-A had significantly fewer chances of having emergency delirium as compared to children in Group-B (p-value